(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The results of the study of synanthropization of 28 grassland habitat types (systematic and florogenetic analyzes, analysis of the alien fraction by time of immigration) are presented. It is established that the synanthropic fraction of grassland habitats of Ukraine is represented by 584 species of vascular plants, which belong to 351 genera, 72 families and 3 divisions. The spectrum of the leading families is dominated by Asteraceae, Brassicaceae, and Poaceae. The range of leading genera is not clearly defined, the leading positions are occupied by the genera Atriplex and Veronica (11 species each). The alien faction is based on species associated with the Mediterranean (80 species), Asian (42) and the Mediterranean and Eastern Turan (38) regions. The synatropic fraction of grassland flora is dominated by apophytes (53.8 %). Kenophytes are prevaile (58.8 %) by the time of immigration. Plantago lanceolata (25 habitat types, 92.6 % of the total number) and Veronica arvensis (18 types, 66.6 %), Erigeron annuus and Lactuca serriola (17 types, 60.7 %) are characterized by the widest habitat range among apophytes and kenophytes respectively. Symphyotrichum ciliatum has the highest average cover (53 %). It is established that all studied grassland habitats of Ukraine are characterized by a certain degree of synanthropization. High synanthropization index (IS) was found in three habitat types: X36 (46.0), R1C (45.4), R13 (41.0). The lowest IS is revealed in habitat types R44 (8.7) and R56 (14.0). The number of kenophytes in the floristic spectrum is 5.7% of the total number of species, which generally corresponds to this figure for European grasslands (6.5%). In general, desert steppes (R1C), continental inland salt steppes (R62), semi-desert salt pan (R64) and depressions (pody) of the Steppe zone (X36) were the most synanthropized, while mountain grasslands were the least synatropized. Thus, there is a trend of decreasing synanthropization in the direction from grassland habitats of the southern regions of Ukraine to the northern and mountainous.